Rubus pseudofagifolius (subg. Lampobatus, Rosaceae), a replacement name for a Mexican bramble species and its lectotypification - Wang, Huanchong; Sun, Hang (Phytotaxa, 2014)
Rubus Linnaeus (1753: 492), belonging to the monotypic tribe Rubeae of the subfamily Rosoideae (Potter et al. 2007), is one of the largest genera in the rose family (Rosaceae). The genus occurs in all continents except Antarctica (Lu & Boufford 2003, Wang et al. 2013). Rubus is a taxonomically notoriously complex group; its species circumscription is complicated by hybridization, polyploidy, agamospermy, and lack of a universal species concept (Weber 1996).